2012
DOI: 10.1002/asi.22636
|View full text |Cite
|
Sign up to set email alerts
|

Intended and unintended consequences of a publish‐or‐perish culture: A worldwide survey

Abstract: How does publication pressure in modern‐day universities affect the intrinsic and extrinsic rewards in science? By using a worldwide survey among demographers in developed and developing countries, the authors show that the large majority perceive the publication pressure as high, but more so in Anglo‐Saxon countries and to a lesser extent in Western Europe. However, scholars see both the pros (upward mobility) and cons (excessive publication and uncitedness, neglect of policy issues, etc.) of the so‐called pu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
110
0
13

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 226 publications
(125 citation statements)
references
References 44 publications
2
110
0
13
Order By: Relevance
“…The ratio of studies concluding in favor vs. against a tested hypothesis increases, moving from the physical, to the biological and to the social sciences, suggesting that research fields with higher noise-to-signal ratio and lower methodological consensus might be more exposed to positive-outcome bias (5,8,9). Furthermore, multiple independent studies suggested that this ratio is increasing (i.e., positive results have become more prevalent), again with differences between research areas (9)(10)(11), and that it may be higher among studies from the United States, possibly due to excessive "productivity" expectations imposed on researchers by the tenure-track system (12)(13)(14). Most of these results, however, are derived from varying, indirect proxies of positive-outcome bias that may or may not correspond to actual distortions of the literature.…”
mentioning
confidence: 99%
“…The ratio of studies concluding in favor vs. against a tested hypothesis increases, moving from the physical, to the biological and to the social sciences, suggesting that research fields with higher noise-to-signal ratio and lower methodological consensus might be more exposed to positive-outcome bias (5,8,9). Furthermore, multiple independent studies suggested that this ratio is increasing (i.e., positive results have become more prevalent), again with differences between research areas (9)(10)(11), and that it may be higher among studies from the United States, possibly due to excessive "productivity" expectations imposed on researchers by the tenure-track system (12)(13)(14). Most of these results, however, are derived from varying, indirect proxies of positive-outcome bias that may or may not correspond to actual distortions of the literature.…”
mentioning
confidence: 99%
“…A despeito da variedade de meios de comunicação, a forma de publicação científica que tem recebido maior atenção nas últimas décadas é o artigo publicado em periódicos indexados com revisão pelos pares, ou peer review (McGrail et al, 2006;Parker et al, 1998;Starbuck, 2005;Van Dalen & Henkens, 2012). Em termos gerais, o foco em artigos publicados em periódicos indexados ganhou essa proeminência institucional por proporcionar a execução dos seguintes processos: (a) o registro da quantidade de citações realizadas que fazem referência a um artigo em particular, que pode indicar a recepção e impacto do trabalho publicado; (b) o cálculo do fator de impacto da revista, realizado com base na extração da média de citações dos artigos publicados em um periódico específico, dentro de um período determinado de tempo; e (c) a estratificação das publicações, particularmente por meio de listas (ou rankings), que permite a classificação das revistas de acordo com o fator de impacto, a percepção de qualidade ou o prestígio do periódico.…”
Section: Publicações Científicas Produtividade E Perfil De Acadêmicosunclassified
“…Avaliação de desempenho de acadêmicos, orientação do sistema de promoções, remuneração, aquisição de estabilidade (tenure) e acesso a recursos de pesquisa (Rond & Miller, 2005;Starbuck, 2005;Van Dalen & Henkens, 2012) são exemplos de decisões nas quais a publicação científica desempenha um papel relevante. Nesses termos, a publicação de artigos se tornou elemento-chave na avaliação da produtividade científica dos acadêmicos, tendo como suporte as métricas e rankings que foram associados a essa forma de produção acadêmica (Adler & Harzing, 2009;Domingues, 2014;Horta & Santos, 2016;Parker et al, 1998).…”
Section: Publicações Científicas Produtividade E Perfil De Acadêmicosunclassified
See 2 more Smart Citations